Elucidating metabolite and pH variations in stroke through guanidino, amine and amide CEST MRI: A comparative multi-field study at 9.4T and 3T - Kexin Wang; Licheng Ju; Guanda Qiao; Yajie Liang; Yihan Wu; Chengyan Chu; Joshua Rogers; Yuguo Li; Suyi Cao; Valina L. Dawson; Ted M Dawson; Piotr Walczak; et al. (NeuroImage)
This study aims to investigate the variations in guanidino (Guan), amine and amide chemical exchange saturation transfer (CEST) contrasts in ischemic stroke using permanent middle cerebral artery occlusion (pMCAO) and transient MCAO (tMCAO) models at high (9.4T) and clinical (3T) MRI fields. CEST contrasts were extracted using the Polynomial and Lorentzian Line-shape Fitting (PLOF) method. Both pMCAO and tMCAO models were utilized to examine the B1-dependence patterns and pH sensitivity of the different CEST contrasts in ischemic lesions compared to contralateral region. At 9.4T, GuanCEST showed the highest signal in the contralateral hemisphere for both stroke models, followed by lower signals from amideCEST and amineCEST, with maximum signals at B1=1.2 μT for all CEST contrasts. In both stroke models, GuanCEST exhibited a significant decrease of 1.15–1.5 % in stroke lesions compared to the contralateral hemisphere (ΔGuanCEST) at an optimal B1 range of 1.2–1.6 μT at 9.4T. This represents more than double the pH sensitivity compared to amideCEST, which showed a reduction of 0.5–0.62 % under the same B1 conditions. In the tMCAO model, amineCEST increased by 3.85 % in the stroke lesion compared to the contralateral hemisphere at an optima B1 range of 1.6–2.5 μT. In contrast, for the pMCAO model, amineCEST increased by 0.87–1.0 % in the stroke lesion. At lower B1 values (<0.8 μT at 9.4T and <0.4 μT at 3T), the GuanCEST changes in the stroke lesion were dominated by creatine concentration changes, which increased in the pMCAO and remained stable in the tMCAO. While GuanCEST and amineCEST are highly sensitive for delineating stroke lesions, amideCEST is more suitable for precise pH mapping as it is not influenced by metabolite changes within the stroke lesion. Additionally, at low B1 values, amideCEST and GuanCEST can be used to map protein and creatine concentrations separately, since they are independent of pH changes at these lower B1 values. Lastly, amineCEST serves as a highly sensitive MRI contrast for detecting reperfusion damage at high MRI fields.